The benefits of triathlon disciplines in maintaining good health - a review of the literature - Zajkowska-Sierpniak, Aleksandra; Cąkała, Marlena; Kozioł, Magdalena; Podgórniak, Kamila; Szymchel, Michał; Grzegorzak, Filip (Quality in Sport, 2024)
Introduction: A triathlon is a multisport event comprising three individual disciplines: swimming, cycling and running. The event is structured around two transition periods, during which competitors change from one mode of transportation to another. The multidisciplinary nature of triathlon places an exceptional physiological burden on athletes, with modifications to haemodynamic, biochemical, cardiorespiratory and metabolic parameters. Participation in triathlon has been linked with a number of benefits, including improved endurance, body toning and enhanced laboratory results. However, this is not an exhaustive list. Based on the evidence currently available, we will attempt to demonstrate that triathlon and its constituent activities represent an optimal approach for enhancing well-being. Aim of the study: The aim of this study is to demonstrate the impact of swimming, cycling and running on specific organ systems, with a particular emphasis on the components of a triathlon. In the course of our research, we have drawn upon the findings of numerous previous studies, as referenced in the bibliography. Every effort has been made to organize and standardize this knowledge.